2011
DOI: 10.1016/j.cell.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Arrangement of Chromosomes during Prometaphase Facilitates Spindle Assembly

Abstract: Error-free chromosome segregation requires stable attachment of sister kinetochores to the opposite spindle poles (amphitelic attachment). Exactly how amphitelic attachments are achieved during spindle assembly remains elusive. We employed photoactivatable GFP and high-resolution live-cell confocal microscopy to visualize for the first time complete 3-D movements of individual kinetochores throughout mitosis in non-transformed human cells. Combined with electron microscopy, molecular perturbations, and immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
389
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(440 citation statements)
references
References 46 publications
37
389
5
1
Order By: Relevance
“…The original search-and-capture model supposed that KC attachments to MTs are end-on, consistent with the results of Kalinina et al (24), while others observed primarily lateral attachments (14,19,20,23,25). Therefore, we studied how the probability of lateral or end-on attachment varied with MT length and the presence or absence of rotational diffusion in the model (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The original search-and-capture model supposed that KC attachments to MTs are end-on, consistent with the results of Kalinina et al (24), while others observed primarily lateral attachments (14,19,20,23,25). Therefore, we studied how the probability of lateral or end-on attachment varied with MT length and the presence or absence of rotational diffusion in the model (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…The original picture of search and capture posited that MTs undergo dynamic instability nucleated from centrosomes until they form end-on attachments with KCs. Additional effects such as diffusion of KCs (12,15), a bias in MT growth toward chromosomes (16)(17)(18), MT nucleation from KCs (15,21,22), spatial distribution and rotation of chromosomes (15,19,20), and KC size decreases after capture (20) can make search and capture more rapid. MT rotational diffusion and lateral capture were found to be important mechanisms in fission yeast (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This force is thought to be mediated by the polymerization of microtubules against the chromosome and by chromosome-bound motors known as chromokinesins [G] (for review see 132 ). Of these, KIF22 (also known as NOD or KID), a member of the kinesin-10 family, is the most likely mediator of the polar ejection force 133 , although the extent to which KIF22 contributes to chromosome congression is unclear 112,[133][134][135][136][137][138] . Optical trapping microscopy shows KIF22 to be a non-processive motor that steps towards the microtubule plus-end, consistent with a role in mediating the ejection force 139 .…”
Section: Polar Ejection Forcesmentioning
confidence: 99%
“…Upon nuclear envelope breakdown (NEBD), chromosomes attach to the forming spindle and move towards the spindle equator 1 . This motion termed congression 2 results in the alignment of chromosomes at the metaphase plate midway between the two spindle poles.…”
mentioning
confidence: 99%